KAJIAN LIMBAH CANGKANG KERANG SEBAGAI ALTERNATIF BAHAN AMELIORAN DI LAHAN GAMBUT - Mita Setyowati; Chairudin Chairudin (Jurnal Agrotek Lestari, 2018)
Peat soil has a high acidity levels, causing low fertility rate, but can be lowered by amelioration. Ameliorant materials that are widely used today are dolomite and limestone which contains calcium carbonate (CaCO3). All material containing Ca compounds can be used as ameliorant material to neutralize the soil acidity that basically adding Ca and lower Al. Waste shells also have the main ingredients in Ca compounds in the form of calcium carbonate (CaCO3) at higher levels when compared limestone, egg shells and other materials, seen from the level of violence kerang.The aim of this research to assess the utilization of waste shells as an alternative ameliorant material on peatland. Research conducted at the Faculty of Agriculture, University of Teuku Umar, Meulaboh in June 2014 to December 2014. Analysis of the chemical constituents shells held in Baristand Industry Banda Aceh, parameters observed were peat soil pH before and after being given ameliorant waste shells, Ca compound, Na, P, and Mg and micro nutrients (Fe, Cu, Ni, B, Zn and Si) in 100 grams of waste shells. This study was followed by the application of waste shells on spinach crops as an indicator of plant growth and production parameters were observed. The result of this research shows that the content of Ca as a constituent CaCO3 in mussel shells higher than dolomite. Giving flour shells can raise the pH soils. The giving of 1.9 ton ha-1 shell clams flour showed the growth and yield of spinach were not significantly different from shell clams flour showed or dolomite flour at a dose of 3.8 ton ha-1. Shell clams flour can be used as an alternative material ameliorant replacement dolomite. Keywords: ameliorant, peat, Shells clams, spinach